N6-methyladenosine modification of circular RNA circASH2L suppresses growth and metastasis in hepatocellular carcinoma through regulating hsa-miR-525-3p/MTUS2 axis - Dafeng Xu; Yachong Liu; Qiumeng Liu; Ganxun Li; Lu Zhang; Chengpeng Yu; Huifang Liang; Xiaoping Chen; Jinfang Zheng; Jia Song (Journal of Translational Medicine, 2024)
Abstract Background CircRNAs have been demonstrated to play a crucial role in regulating the growth and progression of various cancers, including hepatocellular carcinoma (HCC). Nevertheless, the circRNA's expression pattern and function in HCC need more investigation. Methods Bioinformatics techniques were used to identify differentially expressed circRNAs in HCC. CircASH2L expression in HCC tissues was assessed through qRT-PCR and ISH analysis. To assess circASH2L's impact on HCC progression, a variety of experiments were carried out both in vitro and in vivo, such as CCK8, colony formation, EdU assay, flow cytometry, transwell assay, and xenograft mouse model. Various experimental techniques including qRT-PCR, dual luciferase reporter assay, FISH, RNA pull-down, and RIP experiments were utilized to evaluate the relationship between circASH2L, miR-525-3p, and MTUS2. Additionally, experiments were conducted to explore the impact of m6A modification on circASH2L expression, including RNA stability assay, m6A RNA immunoprecipitation assay (MeRIP), and Co-IP experiments. Results We found that circASH2L was downregulated in HCC tissues and the downregulation of circASH2L was significantly correlated with malignant characteristics as well as poor overall survival of patients with HCC. CircASH2L was found to inhibit cells growth, migration and invasion as well as tumorigenesis and metastasis in vivo. Mechanistically, we established that circASH2L directly interacted with miR-525-3p to enhance MTUS2 expression, subsequently leading to tumor suppression. Moreover, the influence of circASH2L on tumor suppression was attenuated by increasing miR-525-3p levels, and MTUS2 was recognized as an essential intermediary in circASH2L-induced tumor suppression. Additionally, N6−methyladenosine (m6A) modification was identified in circASH2L. Our data suggested that METTL3 was responsible for mediating m6A methylation of circASH2L, ultimately regulating circASH2L expression through the promotion of its degradation. These findings collectively highlight the role of circASH2L as a tumor suppressor through a unique circASH2L/miR-525-3p/MTUS2 axis, shedding light on the significance of m6A modification in regulating circASH2L function. Conclusion The work emphasizes circASH2L as a promising therapeutic target for treating HCC, offering new insights into the role of circRNAs in HCC development.